PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. BANK PERKREDITAN RAKYAT ANA ARTHA PONDOK GEDE BEKASI - Eddy Sanusi Silitonga; Ayu Trianah Destarini (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
The purpose of the study was to determine the effect of leadership style and work environment on employee job satisfaction PT. Bank Perkreditan Rakyat Ana Artha Pondok Gede Bekasi. This research is included in the category of causal associative research using a quantitative approach. The population in this study were employees of PT. Rural Bank Ana Artha Pondok Gede Bekasi, totaling 45 people. By using saturated sampling technique, the researcher took all samples from the population. The research method using simultaneous and partially linear regression analysis. The results showed that simultaneous or partially leadership style and work environment had a positive and significant effect on employee job satisfaction.